Evaluation of fatigue progression during overhead tasks and the effects of exoskeleton assistance - Seemab Zakir; Lorenzo Grazi; Francesco Giovacchini; Nicola Vitiello; Emilio Trigili; Simona Crea (Wearable Technologies)
Upper-limb occupational exoskeletons reduce injuries during overhead work. Previous studies focused on muscle activation with and without exoskeletons, but their impact on shoulder fatigue remains unclear. Additionally, no studies have explored how exoskeleton support levels affect fatigue. This study investigates the effects of assistive profiles on muscular and cardiovascular fatigue. Electromyographic (EMG) and electrocardiographic signals were collected to compute EMG median frequency (MDF), heart rate (HR), and heart rate variability (HRV). Fatigue was assessed using three MDF and HR metrics: relative change (